Lung Atelectasis Secondary to Massive Esophageal Dilation in a Patient With Scleroderma. Issue 4 (2010) - St-Arnaud, Charles; Bouchard, Nicole; Lanthier, Luc
Abstract : Esophageal dilation is a rare complication of scleroderma and CREST syndrome. A case of atelectasis secondary to right inferior bronchus compression by a massively dilated esophagus is described. The authors are unaware of any previous cases of atelectasis secondary to esophageal dilation in scleroderma.